Are Religiosity and Spirituality Associated with Obesity Among African Americans in the Southeastern United States (the Jackson Heart Study)? - Reeves, Roy R. (J Relig Health, 2012)
There are several lines of evidence that suggest religiosity and spirituality are protective factors for both physical and mental health, but the association with obesity is less clear. This study examined the associations between dimensions of religiosity and spirituality (religious attendance, daily spirituality, and private prayer), health behaviors and weight among African Americans in central Mississippi. Jackson Heart Study participants with complete data on religious attendance, private prayer, daily spirituality, caloric intake, physical activity, depression, and social support (n = 2,378) were included. Height, weight, and waist circumference were measured. We observed no significant association between religiosity, spirituality and weight. The relationship between religiosity/spirituality and obesity was not moderated by demographic variables, psychosocial variables, or health behaviors. However, greater religiosity and spirituality were related to lower energy intake, less alcohol use and less likelihood of lifetime smoking. Although religious participation and spirituality were not cross-sectionally related to weight among African Americans, religiosity and spirituality might promote certain health behaviors. The association between religion and spirituality and weight gain deserves further investigation in studies with a longitudinal study design.